Character Education Management Strategies to Address the Negative Impacts of Social Media Use on Youth - Rofik, Mashudi; Narto, Amad; Bhoki, Hermania (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to explore effective character education management strategies to address the negative impacts of social media use on adolescents. This research employed a Systematic Literature Review (SLR) to analyze studies on character education, digital citizenship, and social media, focusing on their impact on adolescents. A qualitative approach was used, synthesizing peer-reviewed journal articles, books, and conference papers published in the last five years from academic databases like Google Scholar, PubMed, and Scopus. Data collection involved selecting relevant studies based on specific keywords and predetermined criteria. The collected data were then analyzed through several stages: first, screening and classifying the selected literature; second, extracting key variables such as research focus, methodology, and outcomes; and third, performing a narrative synthesis to identify recurring themes, patterns, and gaps in current research. The results showed that integrating character education with digital citizenship education is crucial in equipping adolescents with the skills to interact positively online. Furthermore, the role of educators trained in technology and digital ethics is essential to help adolescents manage the psychological impacts of social media. The biggest challenge faced is the lack of a curriculum that explicitly integrates digital citizenship with character education. A phenomenon-based approach has proven effective in addressing this challenge by providing students with real-life experiences. In conclusion, digital-based character education can improve adolescents' skills in managing social media use more responsibly. This research makes an important contribution to the development of a more relevant educational curriculum in the digital era.